COPD? what is that? - Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association, 2015)
Chronic Obstructive Pulmonary Disease is defined as a preventable and treatable respiratory disorder largely caused by smoking, which is characterised by progressive, partially reversible airflow obstruction and lung hyperinflation with significant systemic manifestations and co-morbid conditions. (Management of COPD Clinical Practice Guidelines, Second Edition, 2009).